2000
DOI: 10.1530/eje.0.1430639
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thyroid disease, thyroid dysfunction and thyroid peroxidase antibodies in a large, unselected population. The Health Study of Nord-Trondelag (HUNT)

Abstract: Objective: To examine the prevalence of thyroid disease and dysfunction including thyroid autoimmunity in Norway. Materials and methods: All inhabitants 20 years and older (94 009) in Nord-Trùndelag were invited to participate in a health survey with a questionnaire and blood samples. Results: The prevalence of former diagnosed hyperthyroidism was 2.5% in females and 0.6% in males, hypothyroidism 4.8% and 0.9%, and goitre 2.9% and 0.4% respectively. In both sexes the prevalence increased with age. In individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
286
12
27

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(372 citation statements)
references
References 32 publications
47
286
12
27
Order By: Relevance
“…Although we did not measure urine iodine in our subjects, Italy is classified as a mildly iodine-deficient area, and in the largest proportion of those with thyroid dysfunction the condition is probably associated with thyroid autoimmunity [10]. Indeed the prevalence of thyroid autoantibodies among the Cremona Study participants was similar to that reported in the United Kingdom [11], United States [6], Australia [12], Norway [13], The Netherlands [14] and Denmark [15], all geographic regions with no or mild iodine deficiency.…”
Section: Discussionsupporting
confidence: 49%
“…Although we did not measure urine iodine in our subjects, Italy is classified as a mildly iodine-deficient area, and in the largest proportion of those with thyroid dysfunction the condition is probably associated with thyroid autoimmunity [10]. Indeed the prevalence of thyroid autoantibodies among the Cremona Study participants was similar to that reported in the United Kingdom [11], United States [6], Australia [12], Norway [13], The Netherlands [14] and Denmark [15], all geographic regions with no or mild iodine deficiency.…”
Section: Discussionsupporting
confidence: 49%
“…These percentage, compared to those in the literature, which ranged from 3.4% to 25.6%, is higher. 9,11,12,13,24 Antibodies in patients without vitiligo ranged from 13.9% for women to 2.8% for men 19 . Autoimmune diseases mostly associated with vitiligo were pernicious anemia, ranging from 1.8% to 2.3%, and rheumatoid arthritis, varying from 0.38% to 14%, which are higher than the rates found in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects aged between 60 and 69 years had the highest ORs for prior hyperthyroidism among cases when compared to controls (OR ¼ 1.84; 95% confidence interval ¼ 1.20--2.84; Po0.001). 3,14 DISCUSSION While dysthryoidism has been reported to be associated with sexual dysfunction, 3,14 and thyroid hormone disorders in general have been understood to alter the reproductive axis, 15--17 to the best of our knowledge this is the first large-scale population-based study conducted investigating the relationship between ED and hyperthyroidism. After adjusting for monthly income, geographic location, hypertension, diabetes, coronary heart disease, hyperlipidemia, obesity and alcohol abuse/alcohol dependence syndrome, we found that the OR of prior hyperthyroidism among cases was 1.64 (95% confidence interval ¼ 1.37--1.96, Po0.001) than that of controls.…”
Section: Resultsmentioning
confidence: 92%
“…2 A recently conducted prevalence study in Norway found that 0.9% of all Norwegian men over 20 years old in Nord-Trù ndelag had been diagnosed with hyperthyroidism. 3 Graves' disease accounts for 70% of hyperthyroidism cases, with the age of onset most often occurring during young adulthood 1 and is a genetically linked autoimmune disorder in which the body produces antibodies to its own tissues, which in turn cause the thyroid to produce excess of thyroid hormone. The other 30% of hyperthyroidism cases result from other causes, such as toxic nodular goiters, subacute thyroiditis, exposure to iodine from medications or X-ray dyes and postpartum thyroiditis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation